Development Of The Organizational Structure Of The Employee Management System In An Educational Institution - Sidikova Marguba Ismatovna (Zien Journals, 2024)
This article presents opinions and comments on the development of organizational structures of the personnel management system in educational institutions.
Keywords: Management; Organizational; Structure